Assessing coastal aquifer vulnerability to seawater intrusion using the "GALDIT" method: Application to the Dradère-Souiere coastal aquifer (Northern Morocco) - Bekkour Fouad; Amharref Mina; Essaouini Hind; Bernoussi Abdes Samed (E3S Web of Conferences, 2024)
In terms of land-use planning, and in an attempt to anticipate and preserve what can be preserved, the prevention of salinization of coastal aquifers is an important step to which researchers are devoting more and more effort, notably by studying their vulnerability to seawater intrusion. GALDIT is a method for "index mapping" the vulnerability of coastal aquifers, dedicated to the risks of seawater intrusion. The present study involves assessing and mapping the vulnerability of the Dradère-Souiere coastal aquifer (Northern Morocco) to seawater intrusion using this method.